Alterations in proteoglycan synthesis selectively impair FSH-induced particulate cAMP-phosphodiesterase 4 (PDE4) activation in immature rat Sertoli cells - Levallet, Guénaëlle; Levallet, Jérôme; Bonnamy, Pierre-Jacques (Biochimica et biophysica acta, 2007)
FSH-induced upregulation of cAMP-PDE4 activities was decreased in cultured Sertoli cells when alteration of cell proteoglycans (PGs) metabolism was simultaneously induced either by para-nitrophenyl β- d-xyloside (PNPX) or by sodium chlorate. This effect was restricted to the particulate PDE4 activities and its timing was consistent with the half-life of Sertoli cell PGs. It did not result from alterations in Pde4d variants expression, the major FSH-regulated PDE4 in Sertoli cells. Moreover, lack of changes in the particulate levels of major immunoreactive 75 kDa and 90 kDa PDE4D proteins, corresponding likely to short PDE4D1 and long PDE4D3/D8/D9 isoforms respectively, suggested that the decrease in FSH-stimulated of PDE4 activities in chlorate- and PNPX-treated cells at the end of the 24-h incubation period resulted from the increased reversal of the activated particulate PDE4(D) activities back to unstimulated levels. By controlling FSH-stimulated particulate PDE4 inactivation through a still unknown mechanism (sustained activation of PKA or reduction of phosphoprotein phosphatase activities), cell PGs could be involved in the alteration of cAMP response to FSH accompanying the transition of Sertoli cells from proliferative to non-proliferative differentiated state.